TRUTH AS SACRUM IN TARAS SHEVCHENKO’S CREATIONS - Lytvyn, H. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
In the article it is said of Taras Shevchenko’s opinions about the faith, moral values and hard times of his exile and their influence onto the inner world of the poet. The thoughts of the author are illustrated by the excerpts from Kobzar’s poetry, citations from “Diary” and his letters.